2016
DOI: 10.1039/c5ta06039g
|View full text |Cite
|
Sign up to set email alerts
|

N- and S-doped mesoporous carbon as metal-free cathode catalysts for direct biorenewable alcohol fuel cells

Abstract: N and S dual-doped carbon materials, N-S-CMK-3, are fabricated with >1000 m2 g−1 surface area and uniform mesoporous and macroporous structures, and exhibit outstanding ORR activity and durability in both half cell and direct biorenewable alcohol fuel cell tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 55 publications
3
55
0
Order By: Relevance
“…The most commonly used etching agents such as HF,, NaOH, and PVDF etched SBA‐15 resulted in negative replicated carbons possess highly ordered mesoporous network when compare with other etching agents such as KOH,, K 2 CO 3 , NH 3 . The higher surface area of mesoporous carbon has been reported by Singh et al .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The most commonly used etching agents such as HF,, NaOH, and PVDF etched SBA‐15 resulted in negative replicated carbons possess highly ordered mesoporous network when compare with other etching agents such as KOH,, K 2 CO 3 , NH 3 . The higher surface area of mesoporous carbon has been reported by Singh et al .…”
Section: Introductionmentioning
confidence: 80%
“…In this report, the changes in “n” values could be caused by various factors such as changes in layer roughness, alteration occurred in the oxygen coverage and poor kinetics of peroxide reduction by Pt ring under alkaline conditions. Qiu et al . reported the SBA‐15 template derived 10% HF etched OMC showed the onset potential of 0.76 V, the current density of 2.3 at 0.2 V, the n value of 2.6 and peroxide yield 85% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon materials with sulfur functional groups are efficient in removing heavy metals from aqueous solutions, as well as on bio‐renewable alcohol fuel cells using N and S dual‐doped mesoporous carbon . Liang et al., synthesized N–S codoped graphene for the oxygen reduction process. They found that their material exhibited an outstanding electrochemical ORR catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of high‐activity, CO‐tolerant catalysts (at low cost) to replace Pt‐based catalysts for ORR is a particularly important aim towards practical applications for AEMFCs. Recently, heteroatom‐doped carbon catalysts, such as N‐doped, S‐doped, and P‐doped carbon materials, have been extensively studied and used in the ORR because of their high energy conversion efficiency, environmentally friendly nature, and good stability. Among them, the N‐doped carbon catalyst is the most efficient material and has received much attention.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] However, the high cost and low tolerance for CO have becomeamajor problem,w hich limits the widespread use of Pt-based catalysts in the cathode for the ORR. [12] Therefore, the development of high-activity,C O-tolerant catalysts (at low cost)t or eplace Pt-based catalysts for ORR is ap articularly importanta im towards practical applications for AEMFCs.Recently,heteroatom-doped carbon catalysts,s uch as N-doped, [13][14][15][16][17][18][19][20] S-doped, [21][22][23] and P-doped [24] carbon materials,h ave been extensivelys tudied and used in the ORR because of their high energy conversion efficiency,e nvironmentally friendly nature,a nd good stability.A mong them,t he Ndoped carbon catalyst is the most efficient material and has received much attention. Thep yridine-N and quaternary-N in the carbon matrix, which are electron donors,w ill weaken the OÀOb ond due to the bonding between oxygen and nitrogen and/ort he adjacentc arbona tom, [25] thus improving the ORR catalytic activity of the catalyst.…”
Section: Introductionmentioning
confidence: 99%